The Influence of Examiner Independence, Competence, and Work Experience on Audit Quality at The Inspectorate General of the Audit Board of the Republic of Indonesia - Nahdloddin, Muhammad; Widyasari, Widyasari (Devotion : Journal of Research and Community Service, 2025)
The purpose of this study is to analyze the influence of auditor independence, competence, and work experience on audit quality at the Inspectorate General of the Audit Board of the Republic of Indonesia (BPK RI). The sample for this study consisted of 86 respondents who are examiners at the Inspectorate General of BPK RI, and a non-probability sampling method was used. The type of data utilized is primary data, collected from questionnaires completed by respondents via Google Form. The software used to process the data in this research is IBM SPSS Statistics 26. The results indicate that auditor independence, competence, and work experience have a positive and significant influence on audit quality.